Dynamic Channel Allocation for Wireless ATM - Fei, Wang Li (2000)
This thesis examines distributed Dynamic Channel Allocation (DCA) for the wireless environment through simulation. A wireless ATM network simulator was developed in C language. Performance is judged in terms of Normalized User Payload Throughput (NUPT), Percentage of Frequency Change (PFC), Ratio of Frequency Reuse (RFR), Frame Size (Fs) and Frame Delay (Fd) against traffic load. Some Distributed DCA channel selection strategies are examined, namely Two Frame Transmission (TFT) strategy, Access In Rotation (AIR) strategy and Intensive Access (IA) strategy. The performance of these strategies has been compared with Magic Wand Resource Reservation strategy first. In the Two Frame Transmission (TFT) strategy, Access Point (AP) requests for a channel assignment every two frames, therefore the communication complexity is reduced. The Percentage of Frequency Change (PFC) is reduced by about 50%, but the Normalized User Payload Throughput (NUPT) of TFT strategy is lower than Magic Wand Resource Reservation Strategy first. In the Access In Rotation (AIR) strategy, Mobile Terminals (MT) are divided into two groups, which access in rotation. In AIR strategy, the Normalized User Throughput (N UPT), and reduce Ratio of Frequency Reuse (RFR) are improved. In the Intensive Access (IA) strategy, MTs access with a relative smaller interarrival. The simulation results show that the Normalized User Payload Throughput (NUPT) is improved when IA strategy is applied. A criteria of performance evaluation has been developed to evaluate the performance of wireless ATM network, they are namely Stability factor of physical layer (SPRY), Stability factor of traffic load (St), Ratio of Frequency Reuse (RFR).